(688) System of Economic Plans, Indicators and Norms نظام الخطط الاقتصادية والمؤشرات والمعايير - Gely T.Pavlov (معهد التخطيط القومي, 2026)
ملخص يتألف النظام الاقتصادي الوطني من ثلاثة عناصر أساسية: الخطط الاقتصادية الوطنية، ومؤشرات التنمية الحكومية، والأساس المعياري للتخطيط. وتلعب المعايير والقواعد دورًا محوريًا في هذا النظام، بما في ذلك معايير مدخلات العمل ومعايير استخدام الموارد المادية. تُصنَّف معايير المدخلات وتُحدَّد باستخدام أساليب متنوعة، مع تنظيم العمل على وضع هذه المعايير. وتُعدّ معايير استخدام الموارد المادية في الإنشاءات الرأسمالية وتحديد مخزونات إنتاج المواد الخام من الجوانب الأساسية لهذا الإطار. ويتطلب ذلك تنسيقًا وثيقًا بين الجهات المعنية المركزية والمحلية. The national economic system comprises three key elements: national economic plans, state development indicators, and the normative basis for planning. Standards and norms play a central role in this system, including labor input norms and norms for the utilization of material resources. Input norms are classified and determined using various methods, with the organization of work on setting these norms. Norms for the utilization of material resources in capital construction and the determination of production stocks of raw materials are essential aspects of this framework. This requires close coordination between central and local stakeholders.